Analisis bibliometrik : Kecemasan akademik - Akmala, Nida Azkia (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2024)
This study aims to analyze research trends related to academic anxiety in late adolescents and early adults through a bibliometric approach. Research data was collected from published articles on Google Scholar during the period 2020-2024 using the keywords “Academic Anxiety” and “Academic Anxiety.